CATCH EyoU (Constructing AcTive CitizensHip with European YOUth: Policies, Practices, Challenges and Solutions) - Amnå, Erik (Örebro University, 2018)
Data from the Swedish part of the EU project CATCH EyoU (Constructing AcTive CitizensHip with European YOUth).

The dataset was originally published in DiVA and moved to SND in 2024.

Data från den svenska delen av EU-projektet CATCH EyoU (Constructing AcTive CitizensHip with European YOUth: Policies, Practices, Challenges and Solutions).

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
CATCH EyoU (Constructing AcTive CitizensHip with European YOUth: Policies, Practices, Challenges and Solutions)
Keywords: politics; politik; EU policy; EU-politik; European Union countries; EU-länder; youth policy; ungdomspolitik; Europeisk ungdomspolitik; Europeisk ungdomspolitik; Intervjudata; Intervjudata; Political Science; Statsvetenskap